Evaluation of total phenolics, antioxidant and antiproliferative activities of rhizome extracts from select Zingiberaceae species in South India - Soumya Tumbath; Lakshmipriya Theyyankandi; Jayasree Pullampara Rajamma; Manish Kumar Panickassery Ramakrishnan (International Journal of Phytomedicine, 2016)
Zingiberaceae family members are well known for their ethnobotanical diversity and medicinal importance. This study aimed to evaluate total phenolic content, antioxidant and antiproliferative capacity of five different organic solvent extracts prepared from the rhizomes of Curcuma mutabilis (CM), Curcuma haritha (CH), Curcuma neilgherrensis (CN) and Zingiber anamalayanum (ZA), four hitherto unexplored Zingiberaceae species. Folin-Ciocalteu method and DPPH radical scavenging assay were used to determine respectively the total phenolic content and antioxidant capacity. The antiproliferative activity of the extracts were tested against four human cancer cell lines – K562, REH, Nalm6 and MCF7 to ascertain the IC50 values. Based on total phenolic content, extracts were classified into high-H (> 150 mg GAE/g), medium-M (50-150 mg GAE/g) and low-L (< 50 mg GAE/g) categories. Likewise, percentages of DPPH scavenging activity of extracts were also grouped into high-H (> 50%), medium-M (25 – 50%) and low-L (< 25%) categories. Ten of the twenty extracts exhibited strong cytotoxicity with an IC50 value less than 30 μg/mL. To our knowledge, this is the first report on quantitative assessment of total phenolics, antioxidant and antiproliferative potential of organic solvent extracts of rhizomes from the above mentioned plants.